Characterization of Moderately Thermophilic Bacteria Isolated from Saline Hot Spring in Japan - YOKO KAWASAKI; MADOKA AOKI; YORIYASU MAKINO; HIROYUKI SAKAI; YUKI TSUBOI; JUNKO UEDA; KEIKO WATANABE; SHUICI YAMAMOTO; NORIO KUROSAWA (Indonesian Society for microbiology, 2011)
Twelve strains of moderately thermophilic bacteria were isolated from saline hot springs (55°C, pH 8.3) located in Odaito, Hokkaido, Japan. Based on their 16S rRNA gene sequences, all the strains were closely related phylogenetically each other, indicating that the strains belong to a single species. However, maximal growth temperature and enzymatic characteristics of individual strains were slightly different each other. Some of them grew well at 55°C but others did not. The β-galactosidase activity was also different among the strains. Therefore, the representative strains BEK6 and BEK11 were chosen from individual phenotype groups, and were used for further characterization. The nucleotide sequence of full-length 16S rRNA genes of the representative strains showed 96.6% similarity with Bacillus alveayuensis indicating that the strains belong to a novel species of the genus Bacillus. The cells were Gram positive, and showed both catalase and oxidase activities. The optimal growth temperature and pH of strain BEK6 and BEK11 were around 50°C and 7-8, respectively. They were able to grow in the medium containing 10% NaCl in contrast to B. alveayuensis which can grow in the medium with up to 4% NaCl. The strain BEK11 showed relatively strong protease and amylase activities implying the potential industrial uses of these enzymes under the saline condition.